Optimizing aquaculture land-use: A case study in Dam Doi district, Ca Mau province, Viet Nam - Chi Quang Truong; Van Chieu Nguyen; Hong Thao Nguyen; Thanh Vu Pham (CTU Journal of Innovation and Sustainable Development, 2025)
Land-use planning for aquaculture in accordance with natural and socio-economic conditions in each locality is a necessity for the economic development of the region. This study aims to build a model to optimize the area of aquaculture land for the development of local aquaculture land-use plans. The implementation method relies on the land evaluation, as outlined by FAO (1981), and the linear optimization model. We built the model with the goal of optimizing profit, taking into account factors such as the suitability of the land, the capacity to utilize the land area, the constraints on the desired area of land-use types, labors, and local capital. We built and applied the model in the Dam Doi district of Ca Mau province, optimizing the area for five aquaculture land-use types: ecological shrimp, traditional extensive shrimp, extensive shrimp farming, intensive shrimp, and super intensive shrimp. The three optimal options proposed include: (i) no capital limit; (ii) a limited total investment capital of 4,000 billion VND; and (iii) a limited total investment capital of 3,500 billion VND. In particular, the plan to limit capital to 4,000 billion VND was in line with the district's investment capacity and conditions. The results are references for managers to analyze many solutions for local seafood production development.